The Effect of E-commerce on MSME Performance in the Industrial Sector - Duwi Agustina (Jambura Equilibrium Journal, 2023)
This study aims to find out whether e-commerce have an effect on the performance of MSMEs. The type of research used in research is research with a quantitative approach. E-commerce can benefit as well as benefit because it is cheaper and more efficient The sampling method used was a cluster random sampling technique with a total of 350 respondents of micro-enterprises in Sungailiat District. The analytical techniques used are descriptive statistics and multiple linear regression analysis. The results showed that e-commerce and accounting information systems had a positive and significant effect on the performance of MSMEs in the industrial sector in Sungailiat District. In this study, the characteristics of respondents are based on various types of businesses that are free in form. The research shows that the use of e-commerce plays a good role in improving the performance of general companies, it can be seen that e-commerce helps business actors to market their products widely. The results of this study which states that the use of e-commerce has a positive and significant effect on the acceptance of micro-enterprises, meaning that each unit increase per item score on the use of e-commerce, the acceptance of micro-enterprises will increase unit per item.